The Global Asthma Network rationale and methods for Phase I global surveillance: prevalence, severity, management and risk factors - Ellwood, Philippa; Asher, M. Innes; Billo, Nils E.; Bissell, Karen; Chiang, Chen-Yuan; Ellwood, Eamon M.; El-Sony, Asma; García-Marcos, Luis; Mallol, Javier; Marks, Guy B.; Pearce, Neil E.; Strachan, David P. (The European respiratory journal, 2017)
The Global Asthma Network (GAN), established in 2012, followed the International Study of Asthma and Allergies in Childhood (ISAAC). ISAAC Phase One involved over 700 000 adolescents and children from 156 centres in 56 countries; it found marked worldwide variation in symptom prevalence of asthma, rhinitis and eczema that was not explained by the current understanding of these diseases; ISAAC Phase Three involved over 1 187 496 adolescents and children (237 centres in 98 countries). It found that asthma symptom prevalence was increasing in many locations especially in low- and middle-income countries where severity was also high, and identified several environmental factors that required further investigation. GAN Phase I, described in this article, builds on the ISAAC findings by collecting further information on asthma, rhinitis and eczema prevalence, severity, diagnoses, asthma emergency room visits, hospital admissions, management and use of asthma essential medicines. The subjects will be the same age groups as ISAAC, and their parents. In this first global monitoring of asthma in children and adults since 2003, further evidence will be obtained to understand asthma, management practices and risk factors, leading to further recognition that asthma is an important non-communicable disease and to reduce its global burden.